Biphilic Organophosphorus Catalysis: Regioselective Reductive Transposition of Allylic Bromides via P(III)/P(V) Redox Cycling - Reichl, Kyle D. (J Am Chem Soc, 2015)
We report that a regioselective reductive transposition of primary allylic bromides is catalyzed by a biphilic organophosphorus (phosphetane) catalyst. Spectroscopic evidence supports the formation of a pentacoordinate (σ(5)-P) hydridophosphorane as a key reactive intermediate. Kinetics experiments and computational modeling are consistent with a unimolecular decomposition of the σ(5)-P hydridophosphorane via a concerted cyclic transition structure that delivers the observed allylic transposition and completes a novel P(III)/P(V) redox catalytic cycle. These results broaden the growing repertoire of reactions catalyzed within the P(III)/P(V) redox couple and suggest additional opportunities for organophosphorus catalysis in a biphilic mode.